Identifying the gaps: Knowledge, attitudes and practices of urban-based healthcare providers towards adolescent contraception in Jamaica - Abigail Harrison; Sheree Mair; Helen Trotman (Caribbean Medical Journal, 2023)
Objective: Health care providers (HCPs) may serve as facilitators or barriers to access. We explore the knowledge, attitudes and practices of HCPs in Jamaica to identify gaps which may lead to unmet contraceptive needs for adolescents. Methods: A cross-sectional study design was utilized to collect data from urban-based HCPs through a self-administered questionnaire regarding knowledge of, attitudes towards and practices in adolescent contraception. Summative knowledge and attitude scores were generated. Descriptive and inferential statistical analyses were performed. Results: One hundred and forty-four HCPs participated with a female predominance (n=127; 88.2%) and median (IQR) age of 36 (20) years old. HCPs mean (SD) knowledge score 1.95 (0.81) negatively correlated with age (r= -0.279; p<0.01) and length of time working as an HCP (r= -0.287; p<0.01). Pharmacy staff had lowest mean (SD) scores, 13.4 (4.48); p<0.05. Mean attitude score did not differ significantly by marital status or religion. As HCPs’ length of time in practice increased there was a decrease in the attitude scores (β= -0.380; p<0.05). Conclusion: There is need for capacity-building of HCPs to deliver active contraceptive counselling and provide modern, effective, evidence-based contraceptive services to adolescents in Jamaica. Review and revision of guidelines, policies and laws governing delivery of sexual and reproductive health services is recommended.